Extracellular Vesicles and Damage-Associated Molecular Patterns: A Pandora’s Box in Health and Disease - Picca, Anna; Guerra, Flora; Calvani, Riccardo; Coelho-Júnior, Hélio José; Landi, Francesco; Bernabei, Roberto; Romano, Roberta; Bucci, Cecilia; Marzetti, Emanuele (Frontiers in Immunology, 2020)
Sterile inflammation develops as part of an innate immunity response to molecules released upon tissue injury and collectively indicated as damage-associated molecular patterns (DAMPs). While coordinating the clearance of potential harmful stimuli, promotion of tissue repair, and restoration of tissue homeostasis, a hyper-activation of such an inflammatory response may be detrimental. The complex regulatory pathways modulating DAMPs generation and trafficking is actively investigated for its potential to provide relevant insights into physiological and pathological conditions. Circulating extracellular vesicles (EVs) stemming from altered endosomal-lysosomal system have also been reported in several age-related conditions, including cancer and neurodegeneration, and indicated as a promising route for therapeutic purposes. Along this pathway, mitochondria may dispose altered components to preserve organelle homeostasis. However, whether a common thread exists between DAMPs and EVs generation is yet to be clarified. A deeper understanding of the highly complex, dynamic, and variable intracellular and extracellular trafficking of DAMPs and EVs, including those of mitochondrial origin, is needed to unveil relevant pathogenic pathways and novel targets for drug development. Herein, we describe the mechanisms of generation of EVs and mitochondrial-derived vesicles along the endocytic pathway and discuss their involvement of the endosomal-lysosomal in cancer and neurodegeneration (i.e., Alzheimer’s and Parkinson’s disease).